THE APPLICATION OF NUMERICAL SIMULATION RESULT FOR GEOTHERMAL FINANCIAL MODEL WITH PROBABILISTIC APPROACH: A COMPREHENSIVE STUDY - Cahya Winofa, Nevi
Feasibility of developing geothermal projects is depend on financial return generated from investment. One of the strategies to achieve optimum return is formulating the economics of geothermal projects in a financial model with a high level of confidence. Technical input parameters in the financial model are determined by the amount of available geothermal reserve in the form of a field development scenario. The best method for predicting geothermal reserve is a numerical simulation. The objective of this study is to determine the electricity tariff to generate 30 MW, 60 MW, 110 MW, 50 MW (stepwise), and 90 MW (stepwise) which meet the 50% of Rate of Return value will be equal or not exceed 16% (P50) for certain geothermal field with probabilistic approach. This study started with determining the technical input parameters: the number of production; make-up; and injection wells from each development scenarios based on numerical simulation result. This study was applied to two different fields, 30 MW, 60 MW, and 110 MW in the one field while 50 MW (stepwise) and 90 MW (stepwise) in another field that have been studied by other researchers. Total investment was calculated to generate 30 MW, 60 MW, 110 MW, 50 MW (stepwise), and 90 MW (stepwise), respectively. The result shows that 50% of the estimates will be equal or less than 5.34, 4.74, 4.37, 4.86, and 4.81 Million USD/MW, respectively. The electricity tariff that meet the P50 of Rate of Return at 16% was also calculated, 13.90; 11.75; 11.85; 14.80; and 15.50 cents/kWh, respectively. Then these tariff were evaluated based on Average Cost of Electricity Generation (BPP) on relevant local grid. As a result, the tariff or/and generation cost of 30 MW, 60 MW, and 110 MW scenari